Study Of Fluoride Glasses Devitrification-based Magnesium - Benhamideche, C.; Boutarfaia, A.; Poulain, M. (University of Eloued جامعة الوادي, 2013)
The kinetics of devitrification of fluoride glasses stabilized by magnesium fluoride when heated for some time between the glass transition and melting temperatures. The crystallization kinetics of AlF3-YF3-PbF2-CdF2-MgF2 glass prepared by melting the halide powders were studied by differential scanning calorimetry (DSC). The heating rate varied between 2 and 10 Kmim-1. Arami’s exponent (n) obtained by a non-isothermal method was 1.5 and 2.5 for a AlF3-YF3-PbF2-CdF2-xMgF2 (x= 0, 5, 10) and n > 2.5 for a AlF3-YF3-PbF2-CdF2-15MgF2. According to the classical interpretation of n, these magnitudes correspond to diffusion controlled growth of crystals. The activation energies for crystallization, (E), varied from 195-326 KJ/mol. These results confirm the improved stability of these glasses, which could be used as base glasses for low phonon energy fluoride glass fibers.
Articale in Journal of fundamental and Applied Sciences Vol. 05 N. 01
Keywords: crystallization kinetics, glass transition, DSC, Avrami’s exponent (n), activation energies (E).